2010
DOI: 10.2134/agronj2010.0097
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Sand Particle Shape Complexity using a Dynamic, Digital Imaging Technique

Abstract: Sands used to construct athletic fields and golf course putting greens are characterized in laboratory tests to evaluate their suitability before construction. Many of these tests provide quantitative measurements of soil physical properties; however current evaluation procedures for particle shape rely on subjective visual assessments. The objective was to quantify differences in the particle shape complexity of sands using a dynamic, digital image analyzer, the Camsizer, and correlate those values to current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Lo Guo et al, 2011;Jerolmack et al, 2011). The particle shadows are scanned in 64 directions, providing a precise and detailed analysis of a wide range of particle shapes using CAMSIZER analysis software (e.g., Lo Miller and Henderson, 2010;Patchigolla and Wilkinson, 2010;Jerolmack et al, 2011). Particle shape parameters that are collected in this study include size, roundness, and sphericity (http://www.retsch--technology.com).…”
Section: Shape Analysismentioning
confidence: 99%
“…Lo Guo et al, 2011;Jerolmack et al, 2011). The particle shadows are scanned in 64 directions, providing a precise and detailed analysis of a wide range of particle shapes using CAMSIZER analysis software (e.g., Lo Miller and Henderson, 2010;Patchigolla and Wilkinson, 2010;Jerolmack et al, 2011). Particle shape parameters that are collected in this study include size, roundness, and sphericity (http://www.retsch--technology.com).…”
Section: Shape Analysismentioning
confidence: 99%
“…This is a completely reproducible method that uses clearly defined quantitative measures conforming to international standards of particle shape quantification (International Organization for Standardization, 2006, 2008). The quantitative sphericity and aspect ratio parameters most closely correspond with current qualitative ratings of angularity and sphericity, respectively (Miller and Henderson, 2010). The Camsizer sphericity values and the qualitative angularity ratings are affected by particle surface irregularities, whereas the quantitative aspect ratio values and the qualitative sphericity values describe the overall roundness of the particles.…”
mentioning
confidence: 55%
“…Sand particle shape quantification can also be accomplished using a dynamic, digital imaging method. It has been reported that this technique provides quantitative shape parameters that are not only consistent with those of current shape evaluation methods, but are also more precise and better able to differentiate between varying shape complexities (Miller and Henderson, 2010). The shape parameters provided by this technique include sphericity, symmetry, and aspect ratio.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…This method was reported to be highly correlated with a well-accepted static/quantitative technique using light microscopy (r > 0.9 for both aspect ratio and sphericity) [24]. Particle size distribution (PSD) was determined according to a standardized method developed by the ISO [25].…”
Section: Particle Size Distributionmentioning
confidence: 99%